Structural analysis reveals the formation and role of RNA G-quadruplex structures in human mature microRNAs. Issue 77 (11th September 2018) - Chan, Ka Lung; Peng, Boya; Umar, Mubarak I.; Chan, Chun-Yin; Sahakyan, Aleksandr B.; Le, Minh T. N.; Kwok, Chun Kit
Abstract : By employing interdisciplinary approaches, the prevalence, formation, and effect of RNA G-quadruplex (rG4) structures in human microRNAs (miRNAs) are reported. Abstract : Here we identify hundreds of RNA G-quadruplex (rG4) candidates in microRNAs (miRNAs), characterize the miRNA structure and miRNA–mRNA interactions on several mammalian-conserved miRNAs, and reveal the formation of rG4s in miRNAs. Notably, we study the effect of these rG4s in cells and uncover the role of rG4s in miRNA-mediated post-transcriptional regulation.